Holy Ground: Where Art and Text Meet Studies in the Cultural History of India - Teye Bakker, Hans (Gonda Indological Studies, 2019)
The selected and revised articles in this volume by Hans Bakker deal with Indian culture, religion and history: Hinduism, epigraphy, archaeology, iconography in combination with Sanskrit textual studies. The studies focus on the Skandapurana, Vakataka-Gupta history, Ramtek (Ramagiri), Mansar, Ayodhya, Benares, pilgrimage and holy places (tirtha). Readership: All interested in the cultural history of Northern India of the classical and medieval periods. Sanskritists, historians of religion and historians of Indian art and iconography, as well as historians of Shaivism (Pasupata).